Focus-on-Form, Consciousness Raising Mechanisms and Interaction in the Foreign Language Classroom - Gil, Gloria (The ESPecialist, 2012)
The main objective of this paper is to show some ways in which some mechanisms to make learners’ aware of some formal aspects of the foreing language they are learning can be fostered through classroom language interaction. This study is based on the belief that focus on form tasks in communicative classrooms can help learners’ develop some focus on form mechanisms such as noticing (Batstone, 1994; Schmidt, 1990, 1995), hypothesis forming (Schmidt, 1995), and language manipulating (Batstone, 1994).This article aims, first, at showing the different meanings of the term focus on form. Second, it describes the method and the context. Finally, it provides a discourse analysis of two classroom episodes in order to show how focus on form mechanisms can be interactively developed.